Rio Declaration - Rolston, Holmes, 1932-2025, author; Gale, publisher (Colorado State University. Libraries, 2009)
The United Nations Conference on Environment and Development (UNCED) produced a short document titled Rio Declaration on Environment and Development. The Declaration has since been signed by almost every nation on Earth. It begins: "Human beings are at the centre of concerns..." going on to say that people are entitled to "a healthy and productive life in harmony with nature." Development is the dominating motif; environmental conservation is subsidiary. Some key themes : polluter pays; responsibility for spillover damage; inter-generational equity; public participation; a precautionary approach; environmental impact assessments; differential responsibilities; healthy environments.
Keywords: Rio Declaration on Environment and Development; environmental ethics